Sustainability Indicators as management instruments and Planning Social and Environmental: Analysis of the Municipality of Brejo da Madre de Deus – PE - Macêdo, Helenize de Carlos; Torres, Maria Fernanda Abrantes [UNESP] (Revista Brasileira de Geografia Fisica, 2019)
The discussions on the environmental issue have intensified in the scientific literature and social means due the problems arising from the misuse of natural resources. This situation led to the search for solutions that come promote sustainability on the planet, strengthening the paradigm of sustainable development. In this purpose, the use of tools that enable the study and measurement of socio-environmental systems is fundamental to assist public managers and society the planning and the decision making, aimed at the implementation of public policies and sustainable practices. In this sense, the present study aimed to evaluate social and environmental indicators of Brejo da Madre de Deus – PE Municipality. Through the use of the sustainability dashboard and selection of environmental indicators it was possible to verify the sustainability levels for social, economic and environmental dimensions, totaling an intermediate degree (50.1). These results can be used as tools for the elaboration of public policies that allow an increase of these indexes, improving the quality of life of the population and the environmental preservation in the municipality.
Indicadores de Sustentabilidade como Instrumentos de Planejamento e Gestão Socioambiental: Análise do Município de Brejo da Madre de Deus – PE
Keywords: Planning; Socio-environmental indicators; Sustainability